2015
DOI: 10.1108/jpbm-03-2015-0823
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and emotional processing of brand logo changes

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 52 publications
2
22
0
1
Order By: Relevance
“…The results show that Logo familiarity has positive impact on brand attitude (H2a), which indicates that if consumers are familiar with the brand Logo, they will also have a more positive attitude towards the brand. This result is consistent with the research conclusion of Peterson et al (2015), which found that familiarity with the old Logo affected how consumers perceived the new Logo and how consumers felt about the brand. That is, the more familiar a consumer is with the brand's past Logo, the more likely he or she will be able to detect changes to the new Logo, and such awareness will help to increase consumers' interest and positive attitude towards brands.…”
Section: Discussion and Research Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…The results show that Logo familiarity has positive impact on brand attitude (H2a), which indicates that if consumers are familiar with the brand Logo, they will also have a more positive attitude towards the brand. This result is consistent with the research conclusion of Peterson et al (2015), which found that familiarity with the old Logo affected how consumers perceived the new Logo and how consumers felt about the brand. That is, the more familiar a consumer is with the brand's past Logo, the more likely he or she will be able to detect changes to the new Logo, and such awareness will help to increase consumers' interest and positive attitude towards brands.…”
Section: Discussion and Research Findingssupporting
confidence: 91%
“…In other words, if consumers believe that the Logo is appropriate to the meaning of the brand, they will have a more positive attitude towards the brand. Peterson et al (2015) discussed the relationship between Logo familiarity and brand attitude, and found that familiarity with the old Logo affected how consumers perceived the new Logo. In other words, the more familiar consumers are with a brand's old Logo, the more likely they will be able to perceive changes to the new Logo.…”
Section: Brand Attitudementioning
confidence: 99%
“…While research demonstrates that curiosity has positive implications for consumer behavior (Hill et al., ; Shoham & Pesamaa, ), less is understood about the tactics that marketers can employ to elicit curiosity. Past research exploring the phenomenon has focused on the ability of advertisements (Menon & Soman, ; Park, Mahoney, Kim, & Kim, ), product congruity (Noseworthy, Di Muro, & Murray, ), and changes to the product (Peterson, AlShebil, & Bishop, ) to generate curiosity. The present research answers calls by Rabino, Ince, and Thompson () for research investigating curiosity and extends researchers’ understanding of the role of curiosity in consumer behavior by examining a new driver of curiosity, that of social influence.…”
Section: Discussionmentioning
confidence: 99%
“…Their results are consistent with this study's finding that accumulated brand involvement will positively effect on brand loyalty. However, this study found that brand familiarity has a stronger impact on brand loyalty than brand involvement, which can be understood if we view brand involvement as an individual's perceived relevance of a brand based on his/her inherent needs, values, and interests (Peterson et al, 2015), in contrast to brand familiarity, which reflects the brand's "share of mind," which reflects a consumer's direct and indirect experience with a brand (Mikhailitchenko et al, 2009). Furthermore, we found that brand familiarity predicts brand involvement, which has not been tested in previous studies, thereby advancing the literature on the effects of brand familiarity.…”
Section: Discussionmentioning
confidence: 68%
“…In this study, brand involvement is defined as "the perceived relevance of individual consumers to brands based on their inherent needs, values and interests" (Peterson et al, 2015). As such, brand involvement is conceived of as an external environmental factor that serves as a stimulus that affects consumers' emotional responses to a brand/product.…”
Section: Stimulus and Brand Involvementmentioning
confidence: 99%